Gamified Vocabulary Learning through Kahoot and Quizizz: Effects on EFL Students Engagement and Retention - Burhan, Kristian; Amsa, Helfany; Astuti, Indri; Franchisca, Sherly (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study investigates the effects of gamified vocabulary learning using Kahoot and Quizizz on EFL university students’ engagement and vocabulary retention. Grounded in Self-Determination Theory and cognitive learning theories, the study employed a quasi-experimental pre-test–post-test non-equivalent group design involving 293 non-English-major students enrolled in general English courses at an Indonesian public university. The experimental group received vocabulary instruction through Kahoot and Quizizz, while the control group was taught using conventional vocabulary exercises. Data were collected through vocabulary tests administered at three stages (pre-test, post-test, and delayed post-test), an engagement questionnaire measuring behavioral, emotional, and cognitive engagement, classroom observations, and semi-structured interviews. Quantitative data were analysed using t-tests, one-way ANOVA, repeated-measures ANOVA, and Pearson correlation, while qualitative data were thematically analysed to support interpretation. The findings revealed that students exposed to gamified instruction achieved significantly higher vocabulary gains and demonstrated stronger long-term retention than those in the control group. The experimental group also reported significantly higher levels of engagement across all dimensions. A strong positive correlation was found between engagement and vocabulary retention, indicating that engagement played a mediating role in learning outcomes. The study concludes that pedagogically designed gamified vocabulary learning enhances both engagement and sustainable vocabulary retention in EFL higher education contexts.